Leveraging Tecnology to Enhance Reading Comprehension - Ahmad Fauzan Nafis; Camelia Camelia; Hanif Al Ghiffari; Hayati Eka Pratiwi; Lulu Hairani; Siti Nurhalizah Siregar (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This research discusses the use of technology to enhance reading comprehension. In this digital era, technology has transformed how we receive, process, and use information. Technology provides various tools and applications that support reading instruction, ranging from interactive learning platforms to artificial intelligence-based tools capable of offering real-time feedback. This research explores the role of technology in improving reading comprehension, focusing on personalized learning, the use of digital media, and associated benefits and challenges. Studies show that technology can enhance reading comprehension by providing interactive and engaging learning experiences, as well as instant feedback. However, challenges such as distractions, the need for proper training, and the risk of over-reliance on technology must be addressed. By overcoming these challenges and integrating technology into reading instruction, educators can enhance students' reading skills and prepare them for success in the digital age. In the future, the development of more individualized and adaptive learning tools, as well as the exploration of new technologies such as virtual reality and augmented reality, can provide more immersive and interactive reading experiences. This research aims to provide valuable insights into the future development of technology-based literacy.